2014
DOI: 10.18632/oncotarget.1826
|View full text |Cite
|
Sign up to set email alerts
|

Heme-oxygenase-1 implications in cell morphology and the adhesive behavior of prostate cancer cells

Abstract: Prostate cancer (PCa) is the second leading cause of cancer death in men. Although previous studies in PCa have focused on cell adherens junctions (AJs), key players in metastasis, they have left the molecular mechanisms unexplored. Inflammation and the involvement of reactive oxygen species (ROS) are critical in the regulation of cell adhesion and the integrity of the epithelium. Heme oxygenase-1 (HO-1) counteracts oxidative and inflammatory damage. Here, we investigated whether HO-1 is implicated in the adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 62 publications
4
49
0
Order By: Relevance
“…Recently, the additional anti-tumoral effect of HO-1 in PCa cells has been discovered. Gueron et al have shown that pharmacologically induced or genetic overexpression of HO-1 enhances E-cadherin and β-catenin in vitro and in vivo suggesting its direct effect on the adhesive behavior of cells [114]. Moreover, the interaction between HO-1 and muskelin, a specific factor involved in shaping cellular morphology and adhesive properties and their relocation from the cell membrane towards the cell nuclei has been observed after HO-1 induction [114].…”
Section: Prostate Cancermentioning
confidence: 99%
“…Recently, the additional anti-tumoral effect of HO-1 in PCa cells has been discovered. Gueron et al have shown that pharmacologically induced or genetic overexpression of HO-1 enhances E-cadherin and β-catenin in vitro and in vivo suggesting its direct effect on the adhesive behavior of cells [114]. Moreover, the interaction between HO-1 and muskelin, a specific factor involved in shaping cellular morphology and adhesive properties and their relocation from the cell membrane towards the cell nuclei has been observed after HO-1 induction [114].…”
Section: Prostate Cancermentioning
confidence: 99%
“…One is the increase in cellular motility driven by podoplanin interacting with the ERM proteins-Rho GTPases axis; the second is what we call "effective cohesiveness" in the cells. Effective cohesiveness designates a sensor mechanism or metabolite that would integrate the overall adhesive properties of a cell, and could be regulated by transcriptional and epigenetic mechanisms, protein stability, presence in the plasma membrane and context-specific mechanisms (like, for instance, the properties of the extracellular matrix) (Adhikary et al, 2014;Boulter et al, 2012;Engl et al, 2014;Friedl et al, 2014;Gueron et al, 2014;Marjoram et al, 2014;McGrail et al, 2014;Murali and Rajalingam, 2014;Orgaz et al, 2014;Sadok and Marshall, 2014;Thiery et al, 2012;50 Zegers and Friedl, 2014). If podoplanin is expressed in a cellular context with low effective cohesiveness, it will promote mesenchymal motility that will end up in EMT.…”
Section: Role Of Podoplanin In Emtmentioning
confidence: 99%
“…11 Although the role of HO-1 in cancer is controversial, 12 we have shown that its pharmacologic or genetic upregulation is associated with a less aggressive phenotype in PCa. 13 HO-1 inhibits cell proliferation, migration and invasion, 14 it impairs tumor growth and angiogenesis in vivo and downregulates the expression of target genes associated with inflammation. 14, 15 HO-1 is also implicated in the modulation of cellular adhesion in PCa, upregulating E-cadherin and β -catenin expression, and relocating them to the cell membrane, 13 favoring a more epithelial phenotype.…”
mentioning
confidence: 99%
“…13 HO-1 inhibits cell proliferation, migration and invasion, 14 it impairs tumor growth and angiogenesis in vivo and downregulates the expression of target genes associated with inflammation. 14, 15 HO-1 is also implicated in the modulation of cellular adhesion in PCa, upregulating E-cadherin and β -catenin expression, and relocating them to the cell membrane, 13 favoring a more epithelial phenotype. However, it is yet unclear which are the HO-1 interactors and how it regulates cytoskeleton organization.…”
mentioning
confidence: 99%